In Vitro Inhibition Of Herbal Constituents On Ugt2b7 Enzyme Activity - Abdullah, Nurul Huda (2018)
Herb-drug interaction may cause induction and inhibition of drug metabolizing enzymes which may lead to adverse effect in the body. Two major drug-metabolism enzymes in the human body are cytochrome P450 (CYP) and UDP-glucuronosyltransferase (UGT) enzymes. Whilst CYP-mediated herb-drug interactions have been evaluated in numerous studies, the interactions on UGT enzymes are still limited. In the current study, the in vitro inhibitory effect of thirteen herbal bioactive constituents on one of the most important UGT isoform which is UGT2B7 in human (HLM) and rat liver microsomes (RLM) had been investigated. UGT2B7 is an UGT isoform that is responsible for conjugation of opioids like morphine and codeine, non-steroidal anti-inflammatory drugs such as diclofenac and ketoprofen and an anti-HIV drug, zidovudine (ZDV) with glucuronic acid. In this study, ZDV was used as the probe substrate for evaluating UGT2B7 activity. The herbal bioactive constituents studied for potential UGT2B7 inhibitory potency were andrographolide, arecaidine, arecoline, (+)-catechin, gallic acid, kaempferol-3-rutinoside, mangiferin, mitragynine, quercetin, vanillin, vitexin, isovitexin and zerumbone. The formation of ZDV glucuronide (ZDVG) from ZDV by HLM and RLM was determined using a validated high performance liquid chromatography method. The enzyme kinetics parameters of zidovudine glucuronidation which are Vmax and Km values in HLM were 1450 ± 26.06 pmol/mg/min and 0.88 ± 0.05 mM respectively with an intrinsic clearance value (Vmax/Km) of 1.65 μL/mg/min.